Analisis Penggunaan Limbah Gypsum dan Semen Putih Terhadap Kuat Tekan Bebas Tanah Lempung Kelanauan - Perkasa, Andy Satria Jaya; Sariman, Syahrul; Lebang, Fauzy (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Soil is the most widely used material in the construction of a construction. The development of buildings is currently experiencing a very rapid increase so that the carrying capacity of the soil must be considered but not all the carrying capacity of the soil meets the requirements, such as the carrying capacity of clay soils whose soil types are very fine grained so that the layers of the soil are very soft and cohesive. The soil needs to be stabilized. In this study, gypsum and white cement were used to stabilize the waste. This study aims to determine the value of the free compressive strength of silty clay stabilized with 2% gypsum and varied with white cement to determine the appropriate material composition to increase the bearing capacity of the soil. The percentage of stabilizing material used in this study was 2% gypsum respectively, then varied with white cement: 4%, 8%, 12%. The results of the free compressive strength study obtained the maximum value at the composition of the mixture of 2% gypsum + 8% white cement. that is equal to 0.959 kg/cm²..